Expanding the Assumptions of Symbolic Convergence Theory: Collective Sensemaking of Interfaith Harmony by Teacher and Student Groups - Gayatri, Gati (Journal of Education Culture and Society, 2025)
Thesis. The aim of the study is to identify the deficiency of the assumptions of Symbolic Convergence Theory (Bormann, 1973, 1985) by implementing the theory in the context of collective sensemaking of interfaith harmony by teacher and student groups at different faith elementary schools. The study argues that collective sensemaking of reality can also be affected by organisational values, such as religious values, organisation vision and missions, and structure. Concept. To analyse and interpret the data the study implements the concepts of SCT based on the perspective that collective sensemaking occurs through the process of communication, or practice of discourse, or dramatisation. The process of dramatisation involves exchange of fantasy themes, namely creative and imaginative interpretations, constructed by individuals according to their own purposes. An overlapping of fantasy themes occurring within the dramatisation will develop a common understanding and group cohesiveness. A collection of fantasy themes in group rhetoric indicates the rhetorical vision of the group. Results and conclusions. The results show commonalities and differences between teacher and student groups and between the two faith groups not only those of the fantasy themes created by the groups but also of the values that underlie the collective sensemaking of social diversity. They also show that the structure of each rhetorical group affects the collective sensemaking by defining the character of membership that can limit in rhetorical communities through organisational rules, as well as the vision and mission of the organisation based on religious values adhered to. The study proposes additional assumptions and propositions for SCT and recommends further study or analysis to test and develop SCT.